2022
DOI: 10.1007/s00431-021-04348-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc levels in pediatric patients with COVID-19

Abstract: Zinc has potent immunoregulatory and antiviral effects that are critical for growth, immunity, and neurologic development. The aim of this study was to determine the clinical significance of serum zinc levels in pediatric patients with COVID-19 and to demonstrate its association with disease severity. This prospective observational study was conducted between August 3 and November 15, 2020, in pediatric patients aged 1 month to 18 years with confirmed COVID-19 using reverse transcription-polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(56 reference statements)
1
10
0
1
Order By: Relevance
“…In previous studies, COVID-19 was characterized by a marked decrease in total serum zinc, and clinical data so far indicate that the individual zinc status affects susceptibility, severity, and mortality related to the infection [ 13 , 14 , 15 , 16 , 17 , 20 , 21 ]. The current study adds novel and relevant information on zinc status, and demonstrates that COVID-19 is also associated with a severe decrease in the readily available free zinc pool in serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, COVID-19 was characterized by a marked decrease in total serum zinc, and clinical data so far indicate that the individual zinc status affects susceptibility, severity, and mortality related to the infection [ 13 , 14 , 15 , 16 , 17 , 20 , 21 ]. The current study adds novel and relevant information on zinc status, and demonstrates that COVID-19 is also associated with a severe decrease in the readily available free zinc pool in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding its role in SARS-CoV-2, zinc was found to not only improve the antiviral immune response, but also (i) prevent interaction of SARS-CoV-2 with the angiotensin-converting enzyme 2 (ACE2) on the cell membrane, (ii) affect cellular expression of ACE2, and (iii) impair viral replication (reviewed in [ 9 , 12 ]). Observational studies mostly comparing total serum zinc in mild, moderate, and/or severe COVID-19 patients provided strong indications that disease severity is associated with very low serum zinc levels [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 38 studies, 22 of them were cohort, 5 of them used case–control design, and 11 were cross-sectional. Investigations were conducted in different countries: 9 studies were conducted in Iran [ 3 , 4 , 6 , 9 , 15 , 18 – 21 ], while the remaining were performed in Turkey [ 22 26 ], China [ 7 , 10 , 27 , 28 ], Spain [ 14 , 29 , 30 ], Saudi Arabia [ 1 , 5 , 31 ], France [ 12 , 32 ], Belgium [ 33 ], Korea [ 34 ], Nigeria [ 8 ], India [ 35 , 36 ] Brazil [ 2 ], and Japan [ 37 ]. Twenty-one studies just analyzed the association between Zn and COVID-19 outcomes [ 2 , 4 , 5 , 9 , 12 , 13 , 15 , 18 20 , 22 , 26 , 29 , 30 , 32 , 33 , 35 – 38 ], three studies analyzed the association between Se and COVID-19 outcomes [ 8 , 39 ], one analyzed the association between vitamin A and COVID-19 outcomes [ 40 ], eight studies analyzed the association between vitamin C and COVID-19 outcomes [ 1 , 7 , 10 , 23 25 , 27 , 28 ], and eight studies investigated the association between mixed antioxidant vitamins, Se, and Zn with COVID-19 [ 3 , 8 , 9 , 14 …”
Section: Resultsmentioning
confidence: 99%
“…Another case–control study in Iran [ 19 ] indicated that the median of Zn levels in the cases was lower than the controls (median; IQR 56 ng/ml; 23 vs. 110 ng/ml; 27; respectively) ( P < 0.01). Another case–control study in Turkey [ 22 ] found that serum Zn level was significantly lower among COVID-19 patients (median serum Zn level, 88.5; IQR, 77.2–100 µg/d) compared to the control group (median serum Zn level, 98; IQR, 84–111 µg/dl). Another case–control study in Iran [ 20 ] found that 52% of patients had Zn deficiency, and serum Zn levels of patients were lower than the healthy individuals (67.61 ± 15.10 µg/dl vs. 86.66 ± 11.76 µg/dl; P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation